2007
DOI: 10.2166/wh.2007.136
|View full text |Cite
|
Sign up to set email alerts
|

Fault tree analysis of the causes of waterborne outbreaks

Abstract: Prevention and containment of outbreaks requires examination of the contribution and interrelation of outbreak causative events. An outbreak fault tree was developed and applied to 61 enteric outbreaks related to public drinking water supplies in the EU. A mean of 3.25 causative events per outbreak were identified; each event was assigned a score based on percentage contribution per outbreak. Source and treatment system causative events often occurred concurrently (in 34 outbreaks). Distribution system causati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 28 publications
(6 reference statements)
0
34
0
2
Order By: Relevance
“…However, the presence of high numbers of (oo)cysts in surface water in winter and springtime poses a threat in case of failure of the filtration system. Several drinking water-related outbreaks of giardiosis or cryptosporidiosis occurred after failure of the treatment system (Webber 2002;Wallis et al 1996;Stirling et al 2001;Risebro et al 2007;Pozio et al 1997;MacKenzie et al 1994;Levy et al 1998;Lee et al 2002;Kramer et al 1996;Herwaldt et al 1992;Barwick et al 2000), including an outbreak of waterborne giardiosis in Belgium in 2008 (Radio Télévision Belge Francophone, 2008). Monitoring drinking water for Giardia and Cryptosporidium is not compulsory in Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of high numbers of (oo)cysts in surface water in winter and springtime poses a threat in case of failure of the filtration system. Several drinking water-related outbreaks of giardiosis or cryptosporidiosis occurred after failure of the treatment system (Webber 2002;Wallis et al 1996;Stirling et al 2001;Risebro et al 2007;Pozio et al 1997;MacKenzie et al 1994;Levy et al 1998;Lee et al 2002;Kramer et al 1996;Herwaldt et al 1992;Barwick et al 2000), including an outbreak of waterborne giardiosis in Belgium in 2008 (Radio Télévision Belge Francophone, 2008). Monitoring drinking water for Giardia and Cryptosporidium is not compulsory in Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…This distribution may reflect national variations in surveillance, reporting, monitoring, and investigation of cases and outbreaks, as well as highlighting risk factors such as intensive stocking of farmed animals, environmental contamination, weather conditions and events, discharge of sewage effluent into drinking water sources, and the use of surface water sources. The pathways and host, parasite and environmental factors that determine the risk of infection, and thus public health outcomes, are shown in Figure 1, and how they contribute to waterborne Cryptosporidium outbreaks has been reviewed previously [for example, see 19,22,29]. Risebro and colleagues used a fault tree analysis to examine the contribution and interpretation of events in outbreaks in the EU occurring between 1990 and 2005 [29].…”
Section: Human Infection With the Protozoan Parasitementioning
confidence: 99%
“…The pathways and host, parasite and environmental factors that determine the risk of infection, and thus public health outcomes, are shown in Figure 1, and how they contribute to waterborne Cryptosporidium outbreaks has been reviewed previously [for example, see 19,22,29]. Risebro and colleagues used a fault tree analysis to examine the contribution and interpretation of events in outbreaks in the EU occurring between 1990 and 2005 [29]. Of 31 protozoal drinking water outbreaks, 29 were Cryptosporidium, and most of these outbreaks were attributed to chronic filtration failures or livestock and rainfall in the catchment, contributing concurrently in 11 outbreaks.…”
Section: Human Infection With the Protozoan Parasitementioning
confidence: 99%
See 1 more Smart Citation
“…Cattle has already been considered as a source of water contamination; however, there is little evidence that these animals are the main source of waterborne outbreaks, and that contamination with sanitary effluent from domestic sources is the most likely source (THOMPSON, 2004;SMITH et al, 2006;THOMPSON, 2008). Livestock and rainfall in poorly filtered catchment areas favor the occurrence of outbreaks, especially in areas where environmental concentrations of these protozoans are higher (RISEBRO et al, 2007;PLUTZER et al, 2010a). Heitman et al (2002) investigated the significance of different sources of environmental contamination over 2 years and found that although the prevalence of Giardia spp.…”
Section: Cryptosporidium and Giardia: Waterborne Organisms And Their mentioning
confidence: 99%